“This will never happen in real life”: Cape Town tweens' responses to represented violence in digital games - Koloko, Muya (Centre for Film and Media Studies, 2025)
This dissertation explores how South African children aged between ten and twelve respond to video game violence, and to retaliatory violence in particular. Many video game narratives present retaliation by the playable character as necessary and justified within the narrative and ludus rules of the game. Children's own perspectives on video game violence are rarely examined, especially in the Global South. Using a sequential exploratory mixed methods design, this dissertation investigates to what extent children's understandings of violence in video games are congruent with their understandings of violence in their diverse South African life-worlds. This study argues that South African children have high exposure to violence in both their life-worlds and video games, but that locally-situated gaming practices provide contexts that allow children to differentiate between violence in video games and in their life-worlds. Qualitative observations and interviews in Rondebosch and Khayelitsha showed how participants gained their understandings of video game violence from the ludic and narrative norms in video games; norms presented by parents and other authorities; and the playground norms of their peer groups. Participants drew clear distinctions between representations of violence in video games, and the violence some directly experienced, witnessed, or had heard about. Violence in video games was accepted as fictional and justified by the narrative and rules in the video game, which often included a backstory justifying retaliatory violence. A larger sample of children (n = 217) were surveyed on the potential congruence between support for retaliatory violence in video games and in their life-worlds. A moderate positive correlation (r = 0.424; p < 0.01) was found between support for retaliatory violence in video games and in real life. Despite the narrative resonance of stories involving violent retaliation, and regardless of their socioeconomic background, only children with the highest scores supporting retaliatory violence in video games also supported retaliatory violence in everyday life. This result suggests that the ideas of acceptability of violence presented in video games are not internalised by most children. Overall, children's experiences with video game violence are nuanced and contextual cues from games, peers and caregivers all shape how children perceive video game violence.